Promoting Industrial Heritage: Rejuvenating abandoned industrial buildings for a sustainable urban future (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Countless are abandoned industrial buildings that dominate the skyline of today's urbanized areasand which, thanks to their imposing size, have now become part of all those intrinsic characteristics thatmake up the identity of a place. For many, these buildings are part of a historical moment that saw themas a symbol of progress and wealth, but following the awareness of planetary pollution and the need toreflect on the theme of environmental protection, the situations in which these industrial complexes havebeen abandoned have become increasingly common. To prevent these buildings from being left in astate of neglect, a mere memory now without function, how to redeem them giving industrial buildings anew life in the changing society? Often a demolition and reconstruction process deprives a place of itscollective identity, which could instead be maintained in a strategic operation of “adaptive reuse”. Willbe proposed a reflection on some examples of the successful redevelopment of industrial complexes inEurope will be illustrated a study done in collaboration with Betrice Mazzucco on the regeneration of theindustrial area ex-SAROM on the dock of the city of Ravenna, aiming at the integration of its two coolingtowers into a multifunctional park. The Hammon towers, visible from every point of the city, havebecome for the inhabitants an essential landmark, but they are located within the disused factory areawhich makes their integration impossible into everyday urban life, giving us an ideal example to work on.